Randomised, double-blind controlled trial by dose reduction of implanted intrathecal morphine delivery in chronic non-cancer pain. Issue 7 (31st July 2013) - Raphael, Jon H; Duarte, Rui V; Southall, Jane L; Nightingale, Peter; Kitas, George D
Abstract : Objective: This study aimed to investigate the efficacy of intrathecal morphine in the long term by hypothesising that a reduction of the intrathecal opioid dose following long-term administration would increase the level of pain intensity. Design: Randomised, double-blind, controlled, parallel group trial. Setting: Department of Pain Management, Russells Hall Hospital, Dudley, UK. Participants: 24 patients with non-cancer pain implanted with morphine reservoirs were assessed for eligibility. Interventions: Participants were randomly allocated to one of two parallel groups in which one of the groups had no change in morphine dose and the other group had a small reduction (20%) in dosage every week during a 10-week follow-up. Outcome: Primary outcomes were visual analogue scale (VAS) pain score change and withdrawal from the study due to lack of efficacy. Results: 9 of the patients assessed for eligibility declined to participate in the study. 15 patients were randomised to control (n=5) or intervention (n=10) and included in an intention-to-treat analysis. Owing to worsening of pain, seven patients withdrew from the study prematurely. None knew prior to withdrawal which arm of the study they were in, but all turned out to be in the dose-reduction arm. The calculation of dropout rates between groups indicated a significant statistical difference (p=0.026) and recruitment was ceased. The VAS change between baseline and the last observation was smaller in the control group (median, Mdn=11) than in the intervention group (Mdn=30.5), although not statistically significant, Z=−1.839, p=0.070; r=−0.47. Within groups, VAS was significantly lower at baseline (Mdn=49.5) than at the last observation (Mdn=77.5) for the reduction group, Z=−2.805, p=0.002; r=−0.627 but not for the control group (p=0.188). Conclusions: This double-blind randomised controlled trial of chronic intrathecal morphine administration suggests the effectiveness of this therapy for the management of chronic non-cancer pain. However, owing to the small number of patients completing the study (n=8), further studies are warranted. Trial registration: International Standard Randomised Controlled Trials Centre (ISRCTN 33733462 ).